Development trend and typical applications of industrial big data - Mingfeng HUANG (Dianxin kexue)
The concept and characteristics of industrial big data were introduced,and its development trend was discussed.It meant that industrial big data cluld be widely used in the whole production process in manufacturing enterprises.According to application scenes of research and design,supply,manufacturing,marketing and service,the applications of industrial big data were analyzed and summed up.